Kooris at work : discussions with employers and Koori workers about work, family and cultural needs - Sully, Vincent; Brotherhood of St. Laurence (Fitzroy, Vic. : Brotherhood of St Laurence, 1997)
Annotation pending.
Includes bibliographical references (p. 55-56)
Keywords: Aboriginal Australians -- Employment; Employees -- Australia; Employment